Cytotoxic Activities of Extracts and Isolated Compounds of Some Potential Sumatran Medicinal Plants against MCF-7 and HSC-3 Cell Lines - Meiridha Mutiara Andania; Friardi Ismed; Muhammad Taher; Solachuddin Jauhari Arief Ichwan; Amri Bakhtiar; Dayar Arbain (Institute for Research and Community Services (LPPM) ITB, 2019)
In continuation of our study of Sumatran plants and the bioactivity of their constituents, Stereocaulon halei Lamb (Stereocaulaceae) was extracted and isolated to obtain atranorin (1), lobaric acid (6), and methyl-Î²-orcinol carboxylate (9). We also prepared methanolic extracts of some Sumatran medicinal plants, i.e. Alpinia denticulata, Alpinia malaccensis, Alpinia submutica, Curcuma zedoaria, Centella asiatia, Mangifera indica, Piper crocatum, Mussaenda frondosa, together with previously isolated compounds, i.e. crocatin A (2) and crocatin B (3) from P. crocatum, curcumin (4) from Curcuma longa, demethoxymatteucinol (5) from Sphaerostephanos polycarpus, mangiferin (7) from M. indica, methyl caffeate (8) from Balanophora elongata, tiliroside (10) from Guazuma ulmifolia, and usnic acid from Usnea sp (11). These extracts and compounds were tested for their cytotoxicity against MCF-7 and HSC-3 cell lines by MTT assay (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide). It was found that the IC50 value of atranorin (1), lobaric acid (6), methyl-Î²-orcinol carboxylate (9), and methanolic extract of A. submutica towards the MCF-7 cell line was 208.20 µM, 172.05 µM, 382.60 µM and 70.95 µg/mL, respectively. The IC50 value of lobaric acid (6) and methyl-Î²-orcinol carboxylate (9) against the HSC-3 cell line was 88.92 µM and 260.09 µM, respectively. The other extracts did not show significant cytotoxicity.